Strongly Interacting, Two-Dimensional, Dipolar Spin Ensembles in (111)-Oriented Diamond - Lillian B. Hughes; Simon A. Meynell; Weijie Wu; Shreyas Parthasarathy; Lingjie Chen; Zhiran Zhang; Zilin Wang; Emily J. Davis; Kunal Mukherjee; Norman Y. Yao; Ania C. Bleszynski Jayich (Physical Review X)
Systems of spins with strong dipolar interactions and controlled dimensionality enable new explorations in quantum sensing and simulation. In this work, we investigate the creation of strong dipolar interactions in a two-dimensional ensemble of nitrogen-vacancy (NV) centers generated via plasma-enhanced chemical vapor deposition on (111)-oriented diamond substrates. We find that diamond growth on the (111) plane yields high incorporation of spins, both nitrogen and NV centers, where the density of the latter is tunable via the miscut of the diamond substrate. Our process allows us to form dense, preferentially aligned, 2D NV ensembles with volume-normalized ac sensitivity down to η_{ac}=810  pT μm^{3/2} Hz^{-1/2}. Furthermore, we show that (111) affords maximally positive dipolar interactions among a 2D NV ensemble, which is crucial for leveraging dipolar-driven entanglement schemes and exploring new interacting spin physics.